Defining the para meters of physical activity to improve women’s power abilities of 25–35 years with an average level of physical fitness and different somatotype - Jakubowski, Dzmitry A.; Zimnitskaya, Regina E.; Belski, Ivan V. (Journal of the Belarusian State University. Journalism, 2019)
The article presents a comparative analysis of techniques for improving power abilities in the following organizational forms of physical activity: sport, physical education and fitness. The content of the main components of methods aimed at developing self-power abilities by muscle hypertrophy, self-power abilities by improving the coordination of intramuscular and power endurance of women 25–35 years of different somatotype (asthenic, normosthenic, hypersthenic) having an average level of physical fitness. In this contingent identified indicators of individual and re-highs in core strength exercises. During laboratory pedagogical experiment is identified the parameters of physical activity (weight of heft, number of sets, intervals between rest) aimed at improving the power abilities of women 25–35 years old asthenic, normosthenic and hypersthenic types. These findings make it possible to justify the construction of scientific fitness training women of the first period of mature age in the direction of how to increase the power capacity in particular, and all-round physical fitness in general.